2022
DOI: 10.5430/wjel.v12n6p331
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis on EFL Students’ Thesis Proposal Writing

Abstract: The present research was intended to analyse the errors made by the university students, especially the students in the eight semesters who write thesis proposals. Hence, the main objective of the present research was to investigate types of errors as well as to know the dominant errors which were existed in students’ thesis proposal compositions. This research employed descriptive quantitative study by calculating the number of errors by percentage. There are 42 participants from English Education Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, it indicates an error if students consistently employ the erroneous form. This definition indicates that 'mistake' is a fault that a learner can correct, while an 'error' is a fault that a learner cannot correct (Octaberlina & Muslimin, 2022;Rana et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it indicates an error if students consistently employ the erroneous form. This definition indicates that 'mistake' is a fault that a learner can correct, while an 'error' is a fault that a learner cannot correct (Octaberlina & Muslimin, 2022;Rana et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…). Several studies have been conducted to identify the types of errors and the most frequent errors that appeared in the writing of EFL students (Do, 2023;Fatmawati & Harahap, 2023;Lionny & Kusumadewi, 2022;Octaberlina & Muslimin, 2022). The findings indicated that tense and agreement errors are the most common errors.…”
mentioning
confidence: 99%
“…Concerning the errors in writing, Rahman and Feriyadin (2022) found that Indonesian senior high school students made errors in interference, omission, addition, substitution, and ordering of writing narrative paragraphs. Octaberlina and Muslimin (2022) admitted that addition was the most dominant error in students' thesis proposal writing. Sundari et al, (2021) also found that students made errors in omission, addition, misformation, and misordering of writing recount paragraphs with omission as the most dominant error.…”
Section: Introductionmentioning
confidence: 99%